AD, Volume 7, n° 3, 1982 - Full Issue - journal system (Africa Development, 1982)
CONTENTS L'Afrique face à l'Idéologie de l'Eurafrique : Néo-Colonialisme ouPanafricanisme? Guy MARTIN ........................ 5 Vehicle Assembly Plants in Nigeria as a Means of Technology Transfer/ Acquisition : A Prelim inary Assessment Ikwuakam DIAKU .......................... 22 Ghana: The Failure of a Petty-bourgeois Experiment Kwame Akon NINSIN ....................... 37 Julius Nyerere et la Révolution Africaine Harry GOULBOURNE ........................ 68 On Bourgeois Development Theory - A Critique of Behrendt Ansa ASAMOA ......................... 87 DOCUMENTS - Accelerated Development in Sub-Saharan Africa: An Assessment by the OAU, EC A & ADB Secretariats (EC A edited version) ....109 - Declaration of Tripoli on the World Bank Report entitled «Accelerated Development in Sub-Saharan Africa: An Agenda for Action» ...137 BOOK REVIEWS L'Anthropologie et l'Avenir des Sociétés Pastorales Abdel Wedoul OULD CHEIKH .............. 139 Seeds of Famine: Ecological Destruction and the Development Dilem m a in the W est African Sahel Thomas M. PAINTER ................148 FOCUS ON RESEARCH AND TRAINING INSTITUTES The Institute of Research of the University of Liberia (IRUL) .... 155 BOOKS RECEIVED ......................... 159